Proceedings of the Second Workshop on Natural Language Processing for Internet Freedom: Censorship, Disinformation, and Propaga 2019
DOI: 10.18653/v1/d19-5017
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Propaganda Using Logistic Regression

Abstract: Various propaganda techniques are used to manipulate peoples perspectives in order to foster a predetermined agenda such as by the use of logical fallacies or appealing to the emotions of the audience. In this paper, we develop a Logistic Regression-based tool that automatically classifies whether a sentence is propagandistic or not. We utilize features like TF-IDF, BERT vector, sentence length, readability grade level, emotion feature, LIWC feature and emphatic content feature to help us differentiate these t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Emotional appeal is an important strategy used in propaganda techniques (Da San Martino et al, 2020). (Li et al, 2019) found that features of emotions can be good indicators of a propagandistic and nonpropagandistic fragment in news articles. We explore whether emotion features can help in the identification of the type of propaganda technique in the fragment.…”
Section: Embedding Emotion Featurementioning
confidence: 99%
“…Emotional appeal is an important strategy used in propaganda techniques (Da San Martino et al, 2020). (Li et al, 2019) found that features of emotions can be good indicators of a propagandistic and nonpropagandistic fragment in news articles. We explore whether emotion features can help in the identification of the type of propaganda technique in the fragment.…”
Section: Embedding Emotion Featurementioning
confidence: 99%
“…The combination of linguistic and semantic variables yields an F1 score of 66.16 percent, which is significantly higher than the baseline. [6] Propaganda campaigns attempt to change people's minds in order to further a specific agenda. They take advantage of the Internet's confidentiality, social networks' micro-profiling capabilities, and the ease of organizing and maintaining synchronized networks of records to reach billions of dollars of social network users with persuasive communication that are directly aimed to topics that each individual user is sensitive to, ultimately influencing the outcome on a targeted issue.…”
Section: Related Workmentioning
confidence: 99%
“…Team jinfen (Li et al, 2019) used a logistic regression model fed with a manifold of representations, including TF.IDF and BERT vectors, as well as vocabularies and readability measures.…”
Section: Teams Participating In the Sentence-level Classification Onlymentioning
confidence: 99%